Best practices for cryopreserving sperm in Nonhuman Primates: a systematic review and meta-analysis - Niloofar Sadeghi; Ndifereke Uboh; Corinna N. Ross; John R. McCarrey; Brian P. Hermann (Scientific Reports)
Abstract Nonhuman primates (NHPs) are in increasing demand as models for preclinical research. The availability of a highly efficient cryopreservation protocol for use with NHP sperm has potential to significantly alleviate this demand and contribute to rapid increases in overall number of NHPs available for biomedical research. Thus, this systematic review assesses the state-of-the-art in NHP sperm cryopreservation and uses meta-analyses to describe the impact of varied cryopreservation approaches on NHP sperm. We searched the literature deposited in PubMed, Scopus, and Web of Science databases through June 2024 to identify data relevant to the effect of sperm cryopreservation on quality of thawed sperm compared to fresh sperm across NHP species. All original NHP studies reporting sperm parameters both before cryopreservation and after thawing were included for analysis. In total, 32 articles were included for qualitative analysis and not surprisingly, all 32 studies demonstrated negative effects of cryopreservation on sperm parameters, Specifically, motility and viability were significantly decreased in thawed NHP sperm. While the method of sperm collection did not have a significant impact on recovery of motile sperm, significant variability was evident between species. Importantly, recovery of motile NHP sperm was greatest following rapid sperm freezing methods. This analysis provides critical insights into future research directions to enhance and optimize cryopreservation protocols in NHPs.